Burmese women migrating into violence : inter partner violence in Mae Sot, Thailand - Girones, Olga Cordon; Resurreccion, Bernadette P.; Doneys, Philippe; Sajor, Edsel E.; Asian Institute of Technology Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2012)
This study addresses the possibilities Burmese women immigrants victims of inter partner violence have in Mae Sot to access safety and free themselves from violent relationships and the barriers and constraints they face. Lacking access to legal coverage in Thailand, the sources of authority for these women are the head of villages and the Burmese community-based organizations1, to which they resort for help when experiencing abuse from their partners. The services in place by these institutions create the possibilities these women have to access safety and to escape from violence. Whether these services offer women long-term solutions is the main question this study seeks to answer. Many factors as a result of the migration experience lead to inter partner violence against Burmese women immigrants in Mae Sot. I will argue that they experience major constraints when trying to leave an abusive partner in Mae Sot due to cultural, institutional, structural and personal barriers. This is the result of the prevalent gender ideologies, norms and values stemming from Burmese culture that shape and inform the possibilities that are rendered possible, as well as those that are not made possible, by the institutions working for them.
Submitted in partial fulfillment of the requirements for the Degree of Master of Sciences in Gender and Development Studies, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2011
Keywords: Violence in women -- Thailand -- Mae Sot; Women immigration -- Thailand -- Mae Sot; Women migrant labor -- Thailand -- Mae Sot